Investigation of the Antitumor Effects of Tamoxifen and Its Ferrocene-Linked Derivatives on Pancreatic and Breast Cancer Cell Lines - Márton Kalabay; Zsófia Szász; Orsolya Láng; Eszter Lajkó; Éva Pállinger; Cintia Duró; Tamás Jernei; Antal Csámpai; Angéla Takács; László Kőhidai (Pharmaceuticals, 2022)
Tamoxifen is a long-known anti-tumor drug, which is the gold standard therapy in estrogen receptor (ER) positive breast cancer patients. According to previous studies, the conjugation of the original tamoxifen molecule with different functional groups can significantly improve its antitumor effect. The purpose of this research was to uncover the molecular mechanisms behind the cytotoxicity of different ferrocene-linked tamoxifen derivates. Tamoxifen and its ferrocene-linked derivatives, T5 and T15 were tested in PANC1, MCF7, and MDA-MB-231 cells, where the incorporation of the ferrocene group improved the cytotoxicity on all cell lines. PANC1, MCF7, and MDA-MB-231 express ERα and GPER1 (G-protein coupled ER 1). However, ERβ is only expressed by MCF7 and MDA-MB-231 cells. Tamoxifen is a known agonist of GPER1, a receptor that can promote tumor progression. Analysis of the protein expression profile showed that while being cytotoxic, tamoxifen elevated the levels of different tumor growth-promoting factors (e.g., Bcl-XL, Survivin, EGFR, Cathepsins, chemokines). On the other hand, the ferrocene-linked derivates were able to lower these proteins. Further analysis showed that the ferrocene-linked derivatives significantly elevated the cellular oxidative stress compared to tamoxifen treatment. In conclusion, we were able to find two molecules possessing better cytotoxicity compared to their unmodified parent molecule while also being able to counter the negative effects of the presence of the GPER1 through the ER-independent mechanism of oxidative stress induction.